Tingkat Ketahanan Hidup Penderita Kanker Nasofaring pada Berbagai Modalitas Terapi Studi Kasus yang Menjalani Terapi Konvensional dan Pengobatan Komplementer Alternatif - Jessica Christanti; Awal Prasetyo (MEDIA MEDIKA INDONESIANA, 2012)
Survival rate of patients with nasopharyngeal cancer on various modalitie: Case study of patients on conventional therapy and Indonesian complementary and alternative medicineBackground: There are no data on survival rate of patients with nasopharyngeal cancer (NPC) on complementary alternative medicine in Indonesia. The aim of this study was to analyze the survival rate of patients with nasopharyngeal cancer (NPC) on conventional (modern) and complementary and alternative medicine (CAM) treatments.Methods: A cross-sectional observational study of 33 NPC patients from each conventional (modern) treatment and CAM group was performed. The guided intervews were conducted to describe CAM treatment in NPC patients by using a validated questionnaire based CAM therapies of California Health Interview Survey 2001. Survival analysis was conducted by the Kaplan-Meir method.Results: Most patients (52.3%) used CAM treatments.Multivitamin and herbal medicines were among the commonly used CAM (52.8%). Kaplan-Meier analysis showed no significant results (p=0.444) between groups. The first and second year of survival rate was comparable between groups (66.6% vs. 54.5%; 45.5% vs 33.3%). Furthermore, the median overall survival (OS) was shown (16; 95% CI: 1.58-8.90) in CAM treatment patients and conventional (modern) treatment (12; 95% CI: 8.477-0.00). The prevalenceratio (PR) obtained in this study was 1.2 (95% CI: 0.79-1.69).Conclusion: CAM treatment on NPC patients had no effect on survival rate compared with conventional (modern) treatment.Keywords: NPC, CAM, survival rateABSTRAKLatar belakang: Saat ini, belum ada data tingkat ketahanan hidup penderita kanker nasofaring (KNF) yang menjalani pengobatan komplementer alternatif di Indonesia. Fakta menunjukkan bahwa pengobatan komplementer alternatif di Indonesia merupakan bagian aktivitas sosial budaya. Penelitian ini menganalisis tingkat ketahanan hidup penderita KNF yang memperoleh pengobatan modern konvensional disertai pengobatan komplementer dan alternatif (PKA).Metode: Penelitian cross sectional dilakukan pada 33 penderita KNF di tiap kelompok yang menjalani PKA dan kelompok yang menggunakan pengobatan modern konvensional di wilayah Semarang dan sekitarnya. Wawancara terpimpin untuk terapi PKA dengan menggunakan California Health Interview Survey 2001 yang telah divalidasi. Tingkat ketahanan hidup dianalisis dengan uji Kaplan Meier.Hasil: Sebanyak (52,3%) penderita menjalani PKA, dimana yang tersering adalah dengan multivitamin dan jamu (52,8%). Tingkat ketahanan hidup kelompok PKA di tahun pertama (66,6%) dan tahun ke-2 (45,4%). Tingkat ketahanan hidup tahun pertama dan kedua kelompok obat konvensional 54,5% dan 33,3%. Analisis Kaplan Meier menunjukkan hasil yang tidak bermakna (p=0,444). Analisis median tingkat ketahanan hidup, penderita kelompok PKA didapatkan nilai 16 (CI 95%:1,581-8,900), dan pada kelompok pengobatan modern konvensional didapatkan nilai 12 (CI 95%: 8,477-0,00). Nilai PR didapatkan 1,158 (CI 95%: 0,792-1,692).Simpulan: Penggunaan PKA dan terapi modern konvensional tidak mempengaruhi tingkat ketahanan hidup penderita KNF.